Effect of the dimensions (width and radius) of the shading ring on the measurement of diffuse solar irradiance with the MEO shading ring measurement method - Pai, Alexandre Dal [UNESP]; Franco, José Rafael [UNESP]; Pai, Enzo Dal [UNESP]; Neto, Ângelo Feracin [UNESP]; Raniero, Matheus Rodrigues [UNESP]; Calça, Marcus Vinicius Contes [UNESP] (AIP Publishing, 2024)
Diffuse irradiance was monitored by the Melo-Escobedo-Oliveira shading ring measurement method (MEO method) and requires the application of two corrections: one geometric and one atmospheric. The latter occurs from the interaction of radiation with atmospheric constituents and is known as circumsolar radiation, which is also obstructed by the ring. Thus, the objective of this work is to verify if geometrical aspects of the shading ring, such as width and radius, interfere in the quantification of these atmospheric corrections. Two Kipp & Zonen pyranometers were used to monitor the diffuse irradiance, one with 10/40 cm (width/radius) and one with 5/20 cm (width/radius). The values measured by the rings were compared with the diffuse irradiance obtained by the difference method. Studies were carried out under all atmospheric sky cover conditions: cloudy sky, partially cloudy sky, and clear sky. The results showed the highest atmospheric corrections were obtained for the clear sky coverage. Despite the two assemblies having the same width/radius ratio of 0.250, the assembly with the largest radius showed the lowest atmospheric correction. The application of atmospheric corrections is conditioned to the geometrical aspects of the ring, mainly the radius, to guarantee the quality of measurements carried out by the shading ring method.